2022
DOI: 10.3390/ijms23147856
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Composition Changes after Selective Nerve Innervation

Abstract: Facial nerve paralysis interferes with mimetic muscle function. To reconstruct natural facial movement, free muscle flaps are transplanted as new muscles. However, it is difficult to maintain resting tonus. A dual innervation technique in which other nerves such as the hypoglossal nerve or contralateral facial nerve are added is often applied. Using 10-week-old rats (n = 10), the masseteric and hypoglossal nerves were cut, and the distal stump of the masseteric nerve and the proximal stump of the hypoglossal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Still, based on in silico, in situ, and in vivo studies, the study by Radke et al [ 31 ] developed and reported a new method for the quantitative chemical exchange saturation transfer (qCEST) technique, a promising bio-sensitive MRI technique, in systems with multiple proton pools, to assess the biochemical composition of the intervertebral discs, allowing for the timely diagnosis of degenerative diseases. Moreover, the validity of the dual innervation technique for the facial paralysis treatment has been reported in a study by Watanabe et al [ 32 ]. The results of immunohistochemical and microarray analysis on the masseter muscle of rats subjected to masseteric and hypoglossal nerves suture, reported oxidative characteristics, supporting the validity of the technique.…”
mentioning
confidence: 99%
“…Still, based on in silico, in situ, and in vivo studies, the study by Radke et al [ 31 ] developed and reported a new method for the quantitative chemical exchange saturation transfer (qCEST) technique, a promising bio-sensitive MRI technique, in systems with multiple proton pools, to assess the biochemical composition of the intervertebral discs, allowing for the timely diagnosis of degenerative diseases. Moreover, the validity of the dual innervation technique for the facial paralysis treatment has been reported in a study by Watanabe et al [ 32 ]. The results of immunohistochemical and microarray analysis on the masseter muscle of rats subjected to masseteric and hypoglossal nerves suture, reported oxidative characteristics, supporting the validity of the technique.…”
mentioning
confidence: 99%